Human Serum Amyloid A Protein Inhibits Hepatitis C Virus Entry into Cells - Cai, Zhaohui (American Society for Microbiology, 2007)
Serum amyloid A (SAA) is an acute-phase protein induced by a variety of inflammatory stimuli, including bacterial and viral infections. SAA was recently found to function as an opsonin for gram-negative bacteria. We report here that SAA inhibited hepatitis C virus (HCV) infection in cultured cells. SAA reduced HCV infectivity in a dose-dependent manner when added during HCV infection but not after virus entry. SAA bound HCV virions and specifically blocked HCV entry but did not affect virus attachment. These findings suggest that SAA functions as part of the host innate immune defense mechanisms against HCV infection in humans.